2017
DOI: 10.1177/1468087417736451
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mixture formation process in a two-stroke boosted uniflow scavenged direct injection gasoline engine

Abstract: The two-stroke engine has the great potential for aggressive engine downsizing and downspeeding because of its double firing frequency. For a given torque, it is characterized with a lower mean effective pressure and lower peak in-cylinder pressure than a four-stroke counterpart. In order to explore the potential of two-stroke cycle while avoiding the drawbacks of conventional ported two-stroke engines, a novel two-stroke boosted uniflow scavenged direct injection gasoline engine was proposed and designed. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Our previous research on the mixture preparation in a two-stroke boosted uniflow scavenged direct injection gasoline (BUSDIG) engine showed that the application of narrowly spaced split injection in conjunction with a bowl piston produced stable rich mixture around the spark plug before the spark ignition. 36…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research on the mixture preparation in a two-stroke boosted uniflow scavenged direct injection gasoline (BUSDIG) engine showed that the application of narrowly spaced split injection in conjunction with a bowl piston produced stable rich mixture around the spark plug before the spark ignition. 36…”
Section: Introductionmentioning
confidence: 99%
“…5 Scavenging process is one of the determinants of two-stroke engine performance, 6 because it not only affects the quality of gas exchange but also influences the fuel spray mixing in the subsequent combustion phase, which is related to the fuel economy and emission of the engine. 7,8 In two-stroke engine, the short time of exchanging gas brings the challenge of scavenging performance, which has become a concerned topic. 9,10 For the PV2S engines, it is necessary to establish a relatively high positive pressure drop between the intake and exhaust ports to ensure the efficient scavenging and sufficient intake flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the advantages of the 2-stroke operation, a novel 2-stroke Boosted Uniflow Scavenged Direct Injection Gasoline (BUSDIG) engine has been designed and extensively researched at Brunel since 2015 [7]. Key designs of the proposed BUSDIG engine, including engine bore/stroke ratio [8], scavenge ports [9][10][11], opening profiles of scavenge ports and exhaust valves [12], intake plenum [13], injection strategies [14,15] and piston shape [16] have been systematically studied to optimise the scavenging performance and charge preparation of the BUSDIG engine.…”
Section: Introductionmentioning
confidence: 99%